(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Grasspea; seed storage protein; SDS-PAGE; trypsin inhibitor; ODAP Bangladesh j. genet. biotechnol. 5 (1&2): 27-31, 2004 (June & December)